Voltage Compensation-Type Current Limiter Based on Hybrid Distribution Transformer for Power Quality Enhancement - Wang, Ruiayo; Wang, Jianhua; Yan, Han; Chen, Weiming; Fan, Yuanliang (EAI Endorsed Transactions on Energy Web, 2026)
This paper presents a voltage compensation-type current limiter based on a hybrid distribution transformer (HDT) structure, which integrates a three-winding transformer, AC/DC converter, DC/AC converter, current-limiting unit, bypass switches, and a series transformer. The HDT operates under four distinct modes: steady-state operation, voltage recovery, active current limiting, and passive current limiting. The proposed system effectively compensates voltage sags and limits fault currents by dynamically switching between these modes. Simulation results demonstrate that the method can quickly restore load-side voltage during upstream voltage sags and efficiently limit fault currents during downstream faults. The proposed strategy ensures continuous and reliable operation of sensitive loads under fault conditions.
Keywords: Current limiting; Hybrid distribution transformer; Power quality; Voltage compensation